Monitoring of Pests on Palm Oil (Elaeis guineensis Jacq.) in Kuantan Singingi Regency, Indonesia - Sigalingging, Govand; M. Amrul Khoiri; Pajri Ananta Yudha (Jurusan Budidaya Perkebunan, 2025)
The oil palm plant is one of the plantation commodities that plays an important role in economic activities in Indonesia. Cultivating oil palm plants as monocultures causes the environment to be favorable for insect pests to attack the plants. To overcome this, it is necessary to observe the types and populations of pests on palm oil plants. This research aimed to obtain information and data regarding the types and populations of pests and insects on palm oil plants (Elaeis guineensis Jacq.) in Kuantan Singingi Regency. The research was conducted from June to August 2024. The research method was a survey method, and plant samples were taken randomly (purposive random sampling). There were 9 sample plots, where each plot was observed on 13 plants, and the total number of plants observed was 117. The observed parameters were the condition of the agroecosystem, the type of pest on the palm oil plants, the percentage of attacked clumps, the percentage of attacked plants, and the intensity of pest attack. The result showed that the found pests were Metisa plana, Orgyia sp., Oryctes rhinoceros, Setora nitens, and Tirathaba mundella. The dominant pests were Metisa plana (208 individuals), Setora nitens (98 individuals), Orgyia sp (129 individuals), and Tirathaba mundella (42 individuals). There were also non-pest insects, Spinaria spinator, Utethesia pulchelliodes, and Creatonotos gangis.